Sugarcane bagasse ash in the compressive strength of concrete - Farfán Córdova, Marlon Gastón (2018)
In this investigation, the effect of sugarcane bagasse ash (SBA) on concrete strength of 210 kg/cm2 is evaluated, partially replacing SBA with cement, in proportions of 20 and 40%. The results showed that the compressive strength of the concrete decreased with increasing ash content, below the design mix. Concrete with 20% SBA had better compressive performance at 7 and 28 days of cure, although both were 59% below standard concrete (control). This suggests not recommending SBA for structural use because of its decreased compressive strength.